Genetic Variability of 3′-Proximal Region of Genomes of Orf Viruses Isolated From Sheep and Wild Japanese Serows (Capricornis crispus) in Japan - Shimizu, Kaori; Takaiwa, Asari; Takeshima, Shin-nosuke; Okada, Ayaka; Inoshima, Yasuo (Frontiers in Veterinary Science, 2020)
Orf virus is a prototype species of the genus Parapoxvirus, subfamily Chordopoxvirinae, family Poxviridae. Japanese orf viruses, infecting sheep and wild Japanese serows (Capricornis crispus), have been considered to be genetically closely related based on the sequence identities of the open reading frames (ORFs) 11, 20, and 133 in their genomes. However, since the genome size of orf viruses is about 140 kbp long, genetic variation among Japanese orf viruses remains unclear. In this study, we analyzed the sequences of ORFs 117, 119, 125, and 127 located the 3’-proximal region of viral genome using two strains from sheep and three strains from Japanese serows isolated from 1970 to 2007, and compared them with the corresponding sequences of reference orf viruses from other countries. Sequence analysis revealed that the ORFs 125 and 127, which encode the inhibitor of apoptosis and viral interleukin (IL) -10, respectively, were highly conserved among the five Japanese orf viruses. However, high genetic variability with deletions or duplications was observed in the ORFs 117 and 119, which encode granulocyte macrophage colony-stimulating factor and IL-2 inhibition factor (GIF), and inducer of cell apoptosis, respectively, in one strain from sheep and two strains from Japanese serows. Our results suggest that genetic variability exists in Japanese orf viruses even in the same host species. This is the first report of genetic variability of orf viruses in Japan.